A MÍDIA IMPRESSA E OS ASPECTOS PSICOSSOCIAIS DO ESTUDANTE UNIVERSITÁRIO - Franco, Sandra Lia Rodrigues (2007)
The non specialized printed media shows several pieces concerning university students and this thesis aims to verify which psycho-social aspects are most frequently included. Selected news about university students were chosen from Folha de S. Paulo, O Estado de S. Paulo and A Tribuna newspapers. The news analysis was led by the Ryad Simon s Adaptative Evolution Theory, especially with the concern of adaptative sectors named relational-affective, productive, organic and social-cultural. It was verified that the printed media cares more intensively of the students productive and social-cultural sectors rather than the relational-affective and organic ones. Aiming to investigate the journalists way of thinking about these results, they were requested to fill out a questionnaire and it was verified that the majority of journalists are aware of the productivity and social-cultural sectors relevancy, but still consider all adaptative sectors presence important in their articles.